A New Strategy to Build Electrochemical Enzymatic Biosensors Using a Nanohybrid Material Based on Carbon Nanotubes and a Rationally Designed Schiff Base Containing Boronic Acid - Venegas-Yazigi, D; Venegas-Yazigi, D; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P; Gutierrez-Cutino, M; Gutierrez-Cutino, M (Elsevier B.V., 2024)
We report a nanohybrid material obtained by non-covalent functionalization of multi-walled carbon nanotubes (MWCNTs) with the new ligand (((1E,1′E)-(naphthalene-2,3-diylbis(azaneylylidene))bis(methaneylylidenedene)) bis(4-hydroxy-3,1-phenylene))diboronic acid (SB-dBA), rationally designed to mimic some recognition properties of biomolecules like concanavalin A, for the development of electrochemical biosensors based on the use of glycobiomolecules as biorecognition element. We present, as a proof-of-concept, a hydrogen peroxide biosensor obtained by anchoring horseradish peroxidase (HRP) at a glassy carbon electrode (GCE) modified with the nanohybrid prepared by sonication of 2.0 mg mL−1 MWCNTs and 0.50 mg mL−1 SB-dBA in N,N-dimethyl formamide (DMF) for 30 min. The hydrogen peroxide biosensing was performed at −0.050 V in the presence of 5.0 × 10−4 M hydroquinone. The analytical characteristics of the resulting biosensor are the following: linear range between 0.175 μM and 6.12 μM, detection limit of 58 nM, and reproducibility of 2.0 % using the same nanohybrid (6 biosensors), and 9.0 % using three different nanohybrids. The sensor was successfully used to quantify hydrogen peroxide in enriched milk and human blood serum samples and in a commercial disinfector. © 2023 Elsevier B.V.